UV Spectrophotometric Determination of Duloxetine Hydrochloride - GOWRI SANKAR, D.; HEMANT KUMAR, T.; VAMSI KRISHNA, M. (Asian Journal of Chemistry, 2010)
Simple and sensitive UV spectrophotometric method for the determination of duloxetine hydrochloride having absorption maximum at 290 nm and method have been extended to pharmaceutical preparations. There is no interference from any common pharmaceutical additives and diluents. The method has been statistically evaluated and found to be precise and accurate.